2022
DOI: 10.1002/ijc.34281
|View full text |Cite
|
Sign up to set email alerts
|

CD25: A potential tumor therapeutic target

Abstract: CD25 is the alpha‐chain of the heterotrimer IL‐2 receptor. CD25 is expressed on the surface of both immune and non‐immune cells with different frequencies. For cancers, CD25 is expressed at high levels in many types of hematological malignancies, but at low levels in most solid tumors. CD25 is also highly expressed in activated circulating immune cells and regulatory T cells (Tregs). Infiltration of Tregs in the tumor microenvironment can lead to an imbalanced ratio of effector T cells (Teffs) and Tregs, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 114 publications
0
16
0
Order By: Relevance
“…CD25 is the α-chain of the heterotrimer IL-2 receptor and highly expressed in regulatory T cells(Treg) [40]. In the tumor microenvironment, in ltration of Tregs can cause an imbalance of effector T cells (Teffs) and Tregs, which are associated with the progression of cancer [41]. GM can play an important role in immune response [42].Herein, we demonstrated that CD25 on resting Treg may be a critical moderator between PWY-5989 and LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…CD25 is the α-chain of the heterotrimer IL-2 receptor and highly expressed in regulatory T cells(Treg) [40]. In the tumor microenvironment, in ltration of Tregs can cause an imbalance of effector T cells (Teffs) and Tregs, which are associated with the progression of cancer [41]. GM can play an important role in immune response [42].Herein, we demonstrated that CD25 on resting Treg may be a critical moderator between PWY-5989 and LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…While B cells have been shown to suppress tumor progression, they are also implicated in inducing carcinogenesis and cancer progression [19,20]. CD25 represents the alpha component of the IL-2 receptor complex, exhibiting high expression levels in numerous hematological malignancies while remaining minimally expressed in most solid tumors [21]. Mounting research indicates that CD25 could serve as a catalyst in the proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL2RA is the alpha-chain of the IL-2 receptor and expressed on immune and non-immune cells with different proportions [30]. From the study of Elena de Dios ea al, we obtained that high expression of CD25 and CD69 and related immune checkpoints was associated with a better short and long period cardiac structure and function in patients of post ST-elevation myocardial infarction [31].…”
Section: Discussionmentioning
confidence: 99%